Extending and validating gestUI using technical action research - Parra Gonzalez, Luis Otto (2017)
gestUI is a model-driven method with tool support to define custom gestures and to include gesture-based interaction in existing user software system interfaces. So far, gestUI had been limited to the definition of the same gesture catalogue for all users of the software system. In this paper, we extend gestUI to permit individual users to define their own custom gesture catalogue and redefine some custom gestures in case of difficulty in using or remembering them. After extending gestUI, we applied technical action research from the FP7 CaaS project's Capability Design Tool with the aim of assessing its acceptance in an industrial setting. We also analysed its perceived ease-of-use and usefulness and gestUI's desirability level and user experience. The study shows that the tool can help improve the definition of custom gestures and the inclusion of gesture-based interaction in user interfaces of software systems.